EFEKTIFITAS PENDEKATAN KONSTRUKTIVISME UNTUK MENINGKATKAN PEMAHAMAN SIFAT BENDA PADA MATA PELAJARAN IPA BAGI ANAK KESULITAN BELAJAR - Yosi Dwiverani, Fatmawati, Damri (Jurnal Penelitian Pendidikan Khusus, 2013)
This study originated from the observation, assessment and interview research with third grade teacher, that there is a class III student sex man with learning difficulties, particularly in materials science with basic competencies identify different properties. This is evidenced by the observation and assessment is done, the child suffered misconceptions in interpreting scientific he idea different, the value of the child in understanding the nature of the material objects do not always reach the KKM. To help the child Constructivist approach that researchers use to build children's early knowledge gained through experience.This research uses experimental approach in the form of Single Subject Research (SSR) with ABA design. As the subject of this study is a child sex man with learning difficulties (x) aged 10 years. Data was collected using a skills assessment tool items, event recording format is to calculate how many questions that can be answered by a child, of the 10 questions were given, on condition baseline, the intervention condition using a constructivist approach, and the baseline condition after not again using a constructivist approach. Analysis of the data shows the long baseline conditions is 6 times the data of observations with children are only able to answer 10% of questions on a particular observation and the observation of other children can not answer a question correctly, for 6 days. Intervention condition was 10 times of observation, the first meeting the child is able to answer questions 30%, down 20% and then continued to increase up to 100%, for 10 days. And the conditions are no longer given intervention After 6 times of observation, the child can answer questions about 70% to increase to 100%, for 6 days. Trend toward decreased baseline data (-), the data trend towards increased intervention (+), and the data baseline after discontinuation intervention also increased (+). Based on data analysis, it is concluded that the effect of the intervention using a constructivism approach is effective in improving the ability of understanding the nature of things for kids learning difficulties.